Results and perspectives of cosmic ray mass composition studies with EAS arrays in the Tunka Valley. Issue 5 (May 2016) - Prosin, V V; Budnev, N M; Chiavassa, A; Dyachok, A N; Epimakhov, S N; Fenu, F; Fomin, Yu A; Gress, O A; Gress, T I; Kalmykov, N N; Karpov, N I; Korosteleva, E E; et al.
Abstract: The study of the cosmic ray mass composition in the energy range 10 16 - 10 18 eV is one of the main aims of Tunka-133. This EAS Cherenkov array started data acquisition in the Tunka Valley (50 km from Lake Baikal) in autumn 2009. Tunka-133 provides a measurement of the EAS maximum depth (Xmax ) with an accuracy of about 30 g/cm 2 . Further mass composition analyses at the highest energies (10 17 - 10 18 eV) will be based on the comparison of primary energy measured by the radio method and the densities of charged particles measured by shielded and unshielded detectors. The high duty cycle of the common operation of the new scintillation array (Tunka-Grande) and the radio extension of the experiment (Tunka-REX) will provide a high statistics of events.